An analog electronics companion basic circuit design for engineers and scientists - Hamilton, Scott (Cambridge Univ. Press, 2003)
"Engineers and scientists frequently find themsleves having to get involved in electronic circuit design even though this may not be their specialty. This book is specifically designed for these situations, and has two major advantages for the inexperienced designer: it assumes little prior knowledge of electronics and it takes a modular approach, so you can find just what you need without working through a whole chapter. The first three parts of the book start by refreshing the basic mathematics and physics needed to understand circuit design. Part 4 discusses individual components (resistors, capacitors etc.) while the final and largest section describes commonly encountered circuit elements such as differentiators, oscillators, filters and couplers. A major bonus and learning aid is the inclusion of a CD with the student edition of the PSpice simulation software, together with models of most of the circuits described in the book."--Provided by publisher.
Includes bibliographical references and index
Keywords: Electronics; Analogschaltung